Characterizing the Distribution of Temperature and Normal Stress on Flash Heated Granite Surfaces at Seismic Slip Rates. Issue 5 (24th May 2021) - Barbery, M. R.; Chester, F. M.; Chester, J. S.
Abstract: At seismic slip rates, flash‐weakening can significantly reduce the coefficient of friction, and the magnitude of weakening increases with surface temperature. To quantify the distribution of flash temperature, high‐speed double‐direct shear experiments were conducted on Westerly granite blocks using velocity steps from 1 mm/s to 900 mm/s at 9 MPa normal stress. We employed a high‐speed infrared camera to measure surface temperatures on the moving block during sliding, and utilized a novel sliding‐surface geometry to control the mm‐scale contact history. Following the initial weakening upon the velocity step, the blocks slide at a constant coefficient of friction. Surface temperatures are inhomogeneously distributed across the sliding surface, and increase with displacement. To determine the local normal stress distribution at the mm‐scale, we combine a one‐dimensional thermal model with conventional flash‐weakening models that incorporate a surface temperature‐dependence informed by the controlled, mm‐scale contact history. Early contacts experience local normal stress exceeding 40 times the applied normal stress. As sliding progresses, the local normal stress at the hottest contacts decreases as contact area increases, leading to local normal stresses ranging from 2 to 6 times the applied normal stress on most contacts by 30 mm of slip. Increases in surface temperature, which would decrease the coefficient of friction, are buffered by wear processes that increase contact area and decrease the local normal stress. Treatments of flash heating are advanced by incorporating improved characterization of the state of the sliding surface at the mm and larger scales during sliding. Key Points: Flash surface‐temperature and local normal stress at millimeter and larger scale are inhomogeneous on rock interfaces during seismic slip Mm‐scale contacts comprise ∼10% of the apparent area, flash to 200˚C–400˚C, and support local normal stress 6–20 times the macroscopic stress Dynamic friction remains constant with increasing flash temperature as wear reduces local normal stress and increases contact area with slip